Research progress of vegetative insecticidal protein Vip3 insect-resistant transgenic crops - QUAN Yudong; WU Kongming (浙江大学学报. 农业与生命科学版)
The vegetative insecticidal protein Vip3 produced by Bacillus thuringiensis is a tetramer composed of five domains. Its N-terminal is mainly related to the stability of the structure, while the C-terminal is a potential specific receptor binding region. The Vip3 family of vegetative insecticidal proteins contains 14 holotypes and more than 110 proteins. The proposed mode of action of Vip3 shares some similarities with that of the crystal proteins (Cry proteins), in that both undergo activation (proteolytic processing) in the insect midgut, bind to receptors on the surface of the midgut cells, make pores that lead to cell lysis, and eventually death of the insect. In consideration of different active mechanisms to insects as well as their insecticidal spectrum complementarity, the stack strategy of two kinds of genes (vip3 and cry) has been widely used in development of new insect-resistant transgenic crops worldwide; and Vip3Aa transgenic crops such as maize and cotton have been commercially planted in the United States, Brazil and other countries, in order to delay and manage the Cry protein resistance from some target pests such as Spodoptera frugiperda and others. It has been reported that a high resistance to Vip3 toxins by some insects could be rapidly evolved under the toxin selective press in the laboratory, and also field monitoring to several species has confirmed resistance occurrence of Vip3 in natural environments. Therefore, monitoring and management of target pest resistance are much necessary for industrialization of Vip3 insect-resistant transgenic crops.